The Role of the Mitochondrial Genome in Ageing and Carcinogenesis - Anna M. Czarnecka; Ewa Bartnik (Journal of Aging Research)
Mitochondrial DNA mutations and polymorphisms have been the focus of intensive investigations for well over a decade in an attempt to understand how they affect fundamental processes such as cancer and aging. Initial interest in mutations occurring in mitochondrial DNA of cancer cells diminished when most were found to be the same mutations which occurred during the evolution of human mitochondrial haplogroups. However, increasingly correlations are being found between various mitochondrial haplogroups and susceptibility to cancer or diseases in some cases and successful aging in others.